Operational experience with a seasonally operated full-scale membrane bioreactor plant - Gómez, Marcel; Dvořák, Lukáš; Růžičková, Iveta; Holba, Marek; Wanner, Jiří (Bioresource technology, 2012)
A seasonally operated full-scale membrane bioreactor plant (flat sheet, 0.03 μm) treating municipal wastewater from a recreation facility was monitored for 2 years. In particular, membrane bioreactor operation characteristics and development and changes in extracellular polymeric substances and soluble microbial product concentrations were observed, which were both dependent on volume and quality of incoming wastewater. Microbiological effluent quality, nutrient removal efficiency and activated sludge characteristics were analysed on a regular basis. Correlations between activated sludge quality, extracellular polymeric substance and soluble microbial product concentrations were identified. Pathogen related changes in effluent quality during plant operation were also observed. Nutrient removal efficiency was very good, despite fluctuations in influent flow.
Keywords: dusík; bioreaktory; odpad tekutý - odstraňování; Waste Disposal, Fluid; velkoměsta; Environmental Monitoring; Membranes, Artificial; Biological Oxygen Demand Analysis; Bioreactors; čištění vody; Cities; Water Purification; roční období; Seasons; monitorování životního prostředí; měření biologické spotřeby kyslíku; Nitrogen; membrány umělé